2020
DOI: 10.3390/ijerph17249213
|View full text |Cite|
|
Sign up to set email alerts
|

Socioeconomic Disparities in All-Cause and Cause-Specific Mortality Rates among Municipalities in Japan, 1999–2019

Abstract: Differences in all-cause and cause-specific mortality rates depending on municipal socioeconomic status (SES) in Japan have not been revealed over the last 20 years. This study exposes the difference in 1999 and 2019 using the Vital Statistics. All of the municipalities were grouped into five quintiles based on their SES, and standardized mortality ratio (SMR) of each municipal quintile compared with all of Japan was calculated for all-cause mortality and representative cause of deaths. As a result, although S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…It is known that the age-standardized mortality rates of cancer and cardiovascular diseases, which are the largest causes of death in Japan, are continuing to decrease over recent decades [2]. However, it is known that socioeconomic disparities exist in cause-specific mortality rates or health behaviors and statuses in Japan [3][4][5][6][7]. It was demonstrated that socioeconomic disparities exist in mortality rates among municipalities for some causes of death in Japan in 2019 [7], and as a possible reason for the disparities, socioeconomic differences in health behaviors and statuses were pointed out [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that the age-standardized mortality rates of cancer and cardiovascular diseases, which are the largest causes of death in Japan, are continuing to decrease over recent decades [2]. However, it is known that socioeconomic disparities exist in cause-specific mortality rates or health behaviors and statuses in Japan [3][4][5][6][7]. It was demonstrated that socioeconomic disparities exist in mortality rates among municipalities for some causes of death in Japan in 2019 [7], and as a possible reason for the disparities, socioeconomic differences in health behaviors and statuses were pointed out [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is known that socioeconomic disparities exist in cause-specific mortality rates or health behaviors and statuses in Japan [3][4][5][6][7]. It was demonstrated that socioeconomic disparities exist in mortality rates among municipalities for some causes of death in Japan in 2019 [7], and as a possible reason for the disparities, socioeconomic differences in health behaviors and statuses were pointed out [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this is that low-income municipalities are not necessarily associated with a higher prevalence of diabetes. Municipalities' taxable per-capita income and total population are known to be positively associated in Japan [35]. Urbanization has also been found to be positively associated with diabetes prevalence and mortality in many countries [8,9,14], with high rates of physical inactivity and high-sugar, high-fat diets being identified as possible factors.…”
Section: Disparities In Diabetes Mortalitymentioning
confidence: 99%
“…The author wants to correct the values of the 95% confidence interval of the standardized mortality ratio (SMR) in Table 3 and Table 4 in the following paper [ 1 ].…”
mentioning
confidence: 99%